A Theoretical and Empirical Analysis of a 'State of the Art' Talent Identification Model - Abbott, A.; Collins, D. (High Ability Studies, 2002)
Sport Interactive is a talent identification (TI) program that matches young people to sports based on proficiency on 11 simple physical and performance tasks. An evaluation of the program with Scottish girls (n = 1217, mean age = 12.68 years) and boys (n = 1239, mean age = 12.54 years) identified a number of problems. Firstly, although talent is conceptualized as static, children are evaluated on unstable variables. Additionally, the proposed correlation between proficiency on the Sport Interactive tasks and specific sport aptitude lacks theoretical justification. Finally, problems accrued from the use of Australian norms to interpret the performances of Scottish children. It is concluded that models that are based on a static and uni-dimensional concept of talent are likely to lead to the premature de-selection of many talented children. An alternative TID process that is based on a dynamic and multi-dimensional concept of talent is discussed.